(untitled) (Journal of Parents and Teachers, 2026)
In light of the current state of schools and the education system, which has increasingly placed undue emphasis on verbal language, the author presents a study aimed at gaining a better understanding of the prevalence of different forms of language within school curricula and examining these findings within the new context of the Education Reform. The objectives, methods and results of this study are presented in detail.